Risks, rights or both? Evaluating the common aetiology of negative and positive outcomes for young people to inform youth justice practice - Haines, Kevin (2011)
"The policy and practice of the Youth Justice System of England and Wales has become dominated by risk-focused, offender-first approaches underpinned by the deterministic, reductionist and psychosocially-biased risk factor prevention paradigm. Using the All Wales Youth Offending Strategy and the evaluation of the Welsh Assembly Government's 'Extending Entitlement' youth inclusion strategy as its touchstones, this paper explores a rights- and entitlements-based, children first model of working with young people. This model critiques the management of risks and the purported 'common aetiology' of negative and positive behaviours/ outcomes and evidences the potential advantages of pursuing a proactive, inclusionary, children first, children’s rights agenda when seeking to reduce youth offending." [author's abstract]